Phylogenetic and Maturity Analyses of Sixty Soybean Genotypes Used for DNA Marker Development of Early Maturity Quantitative Trait Loci in Soybean - I Made Tasma; Dani Satyawan; Ahmad Warsun; Muhamad Yunus; Budi Santosa (Balai Besar Penelitian dan Pengembangan Bioteknologi dan Sumber Daya Genetik Pertanian, 2011)
Phylogenetic and Maturity Analyses of Sixty SoybeanGenotypes Used for DNA Marker Development of EarlyMaturity Quantitative Trait Loci in Soybean. I MadeTasma, Dani Satyawan, Ahmad Warsun, MuhamadYunus, and Budi Santosa. The Indonesian soybeanproductivity is still very low with the national average of 1.3t/ha. One means to improve national soybean productivity isby manipulating harvest index by cultivating very earlymaturing soybean cultivars. Development of early maturingsoybean cultivars can be expedited by using marker-aidedselection. The objective of this study was to select parentallines having contrasted maturity traits and selected parentsmust be genetically distance. The parents then were used todevelop F2 populations for detecting early maturity QTL insoybean. Maturity tests of 60 soybean genotypes wereconducted at two locations, Cikeumeuh (Bogor) and Pacet(Cianjur) using a randomized block design with threereplications. Genomic DNA of the 60 genotypes wereanalyzed using 18 SSR markers and genetic relationship wasconstructed using the Unweighted Pair-Group MethodArithmatic through Numerical Taxonomy and MultivariateSystem program version 2.1-pc. Results showed that the 60genotypes demonstrated normal distribution in bothlocations for days to R1 (32-48d), days to R3 (35-55d), days toR7 (75-92d), and days to R8 (78-99d). Four early maturinggenotypes and three late genotypes were obtained. TotalSSR alleles observed were 237 with average allele per locusof 12.6 (3-29), and average PIC value of 0.78 (0.55-0.89).Genetic similarity among genotypes ranges from 74.8-95%.At similarity level 77% divided the genotypes into six clusters(the four selected early maturing genotypes located inclusters III and IV, while the three late genotypes located incluster II). Based on maturity data, pubescent color, andphygenetic analysis seven parents were selected (four earlymaturing genotypes B1430, B2973, B3611, B4433 and threelate genotypes B1635, B1658, and B3570). Twelve F2populations were developed with the aid of SSR markersSatt300 dan Satt516. Two of the populations will be used todevelop DNA markers for earliness in soybean.